Direct visualization of pre-protamine 2 detects protamine assembly failures and predicts ICSI success. (28th February 2022) - Rezaei-Gazik, Maryam; Vargas, Alexandra; Amiri-Yekta, Amir; Vitte, Anne-Laure; Akbari, Arvand; Barral, Sophie; Esmaeili, Vahid; Chuffart, Florent; Sadighi-Gilani, Mohammad Ali; Couté, Yohann; Eftekhari-Yazdi, Poopak; Khochbin, Saadi; et al.
Abstract: Histone-to-protamine transition is an essential step in the generation of fully functional spermatozoa in various mammalian species. In human and mouse, one of the two protamine-encoding genes produces a precursor pre-protamine 2 (pre-PRM2) protein, which is then processed and assembled. Here, we design an original approach based on the generation of pre-PRM2-specific antibodies to visualize the unprocessed pre-PRM2 by microscopy, flow cytometry and immunoblotting. Using mouse models with characterized failures in histone-to-protamine replacement, we show that pre-PRM2 retention is tightly linked to impaired nucleosome disassembly. Additionally, in elongating/condensing spermatids, we observe that pre-PRM2 and transition protein are co-expressed spatiotemporally, and their physical interaction suggests that these proteins act simultaneously rather than successively during histone replacement. By using our anti-human pre-PRM2 antibody, we also measured pre-PRM2 retention rates in the spermatozoa from 49 men of a series of infertile couples undergoing ICSI, which shed new light on the debated relation between pre-PRM2 retention and sperm parameters. Finally, by monitoring 2-pronuclei embryo formation following ICSI, we evaluated the fertilization ability of the sperm in these 49 patients. Our results suggest that the extent of pre-PRM2 retention in sperm, rather than pre-PRM2 accumulation per se, is associated with fertilization failure. Hence, anti-pre-PRM2 antibodies are valuable tools that could be used in routine monitoring of sperm parameters in fertility clinics, as well as in experimental research programmes to better understand the obscure process of histone-to-protamine transition.